Monitoring of time stability of antimicrobial effect of nisin-based pharmaceutical compositions with resistance inhibitors - Osolodchenko, Tetyana; Andreeva, Iryna; Martynov, Artur; Zavada, Nadiya; Batrak, Olena; Ryabova , Iryna (Annals of Mechnikov's Institute, 2024)
Introduction. The combination of nisin with resistance inhibitors, which do not have a direct antimicrobial effect but bind bacterial resistance factors in one way or another, restoring their sensitivity to classical antibiotics, is a promising area of medical science. However, combinations of these agents face the problem of drug stability, preservation of its therapeutic properties, especially antibacterial action. The aim of the work to study the stability of the antibacterial effect of pharmaceutical compositions based on nisin, diclofenac sodium and amlodipine for the treatment of infectious and purulent inflammatory diseases over time. Materials & methods. The antimicrobial activity of 1.0 % aqueous solutions of unmodified and modified nisin with chelating agents was determined. Modified nisin was obtained by acylation of nisin with acetic anhydride. Diclofenac sodium and amlodipine were used as the chelating agents. For the microbiological study of the investigated substances, reference test cultures of gram-positive and gram-negative bacteria belonging to different taxonomic groups were used: The antimicrobial activity of the test substances was determined by the diffusion method of “wells” with the measurement of the diameters of the zones of inhibition of microbial growth. Results & discussion. It was found that after storage for 1 month of the pharmaceutical composition of unmodified nisin with diclofenac sodium, its moderate antimicrobial effect against both test strains of gram-positive microorganisms was maintained. After storage for 2 months, the antimicrobial effect of the double composition of nisin with diclofenac sodium decreased within the range of moderate and decreased to weak after 3 months of observation. After 3 months of storage, this composition did not show any antimicrobial effect against all the test strains of gram-negative microorganisms and C. albicans ATCC 885-653. The composition of 1.0% aqueous solutions of unmodified nisin and amlodipine after 1 month of observation also maintained a moderate antimicrobial effect against both test strains of gram-positive microorganisms, as well as against E. coli ATCC 25922 and P. aeruginosa ATCC 27853. After 2 months of observation, the antimicrobial effect of the double composition of unmodified nisin with amlodipine against S. aureus ATCC 25923, B. subtilis ATCC 6633 and E. coli ATCC 25922 continued to decrease within the moderate range. As for the rest of the test strains of gram-negative microorganisms and C. albicans ATCC 885-653, no antimicrobial effect was observed after 2 months of observation. The triple combination of 1.0% aqueous solutions of unmodified nisin, diclofenac sodium and amlodipine maintained moderate antimicrobial activity against both gram-positive microorganisms during all 3 months of observation, although the effect slightly decreased during the observation period. Among Gram-negative microorganisms, the slowest decrease in susceptibility to the triple combination of unmodified tetnisin with diclofenac sodium and amlodipine was observed in the test strain E. coli ATCC 25922. The ternary combination of 1.0% aqueous solutions of unmodified nisin, diclofenac sodium and amlodipine maintained moderate antimicrobial activity against both gram-positive microorganisms during all 3 months of observation, although the effect slightly decreased during the observation period. After storage for 1 month, the antimicrobial activity of the double formulations of acetylated nisin with both diclofenac sodium and amlodipine against all the studied reference test strains remained almost at the same level, but during further storage, the level of their antimicrobial effect gradually decreased. The antimicrobial effect of the ternary composition of acetylated nisin with diclofenac sodium and amlodipine decreased from high to moderate against S. aureus ATCC 25923 after 1 month of storage, and against B. subtilis ATCC 6633 - after 2 months. With further storage for 3 months, the level of antimicrobial effect of the triple composition of acetylated nisin with diclofenac sodium and amlodipine slowly decreased within the moderate range. For all the test strains of gram-negative microorganisms studied, the antimicrobial effect of the ternary composition of acetylated nisin with diclofenac and amlodipine remained moderate up to 2 months of observation and decreased to weak after 3 months of storage. Conclusion. Thus, according to the results of studying the stability of the antimicrobial effect of compositions based on unmodified and acetylated nisin with diclofenac sodium and amlodipine by keeping them under normal conditions in real time for 3 months, a decrease in their antimicrobial effect was found in relation to all the studied reference strains of microorganisms, while the antimicrobial effect of compositions with acetylated nisin decreased somewhat more slowly than with unmodified nisin. Taking into account the results obtained, it is advisable to use components in pharmaceutical compositions aimed at improving the stability of the antimicrobial properties of pharmaceutical compositions of nisin with resistance inhibitors. Key words: stability of antimicrobial effect, nisin, acetylated nisin, diclofenac sodium, amlodipine, pharmaceutical compositions, microorganisms